Differential expression of connective tissue growth factor in microglia and pericytes in the human diabetic retina. Issue 8 (16th July 2004) - Kuiper, E J; Witmer, A N; Klaassen, I; Oliver, N; Goldschmeding, R; Schlingemann, R O
Abstract : Background/aim: Connective tissue growth factor (CTGF) stimulates extracellular matrix formation, fibrosis, and angiogenesis. It has a role in the pathogenesis of diabetic nephropathy and possibly in diabetic retinopathy (DR): in cultured retinal vascular cells CTGF is induced by VEGF-A. To further characterise this role the authors investigated CTGF expression in normal and diabetic human retina. Methods: CTGF expression patterns were studied by immunohistochemistry in the retina of eyes of 36 diabetic persons and 18 non-diabetic controls and compared with markers of endothelial cells (CD31, PAL-E), pericytes (NG2), astrocytes (GFAP), and microglia (CD45). Results: In the retina, distinct and specific staining of CTGF was observed in microglia, situated around or in close vicinity of retinal capillaries. In the control cases, sporadic staining of pericytes was also observed within the vascular wall. In contrast, in the retina of people with diabetes, CTGF staining in microglia was decreased and staining in pericytes was increased. This pattern of predominantly pericyte staining was observed in 20 out of 36 diabetic cases and in one out of 18 controls. The altered CTGF staining patterns in the diabetic cases did not correlate to staining of PAL-E, a marker of retinal vascular leakage associated with DR. Conclusions: The study shows that CTGF is expressed in microglia in the normal retina whereas in a large subset of diabetic persons, CTGF expression shifts to microvascular pericytes. This altered CTGF expression pattern appears unrelated to manifest DR and may therefore represent a preclinical retinal change caused by diabetes. The results suggest a distinct, but as yet unidentified, role of CTGF in the pathogenesis of diabetic retinopathy.